(untitled) (Cardiovascular Journal, 2010)
Background: In recent years, high thoracic anaesthesia (HTEA) combined with general anaesthesia has been extensively studied in patients undergoing coronary artery bypass graft surgery with or without cardiopulmonary bypass. Off-pump coronary artery bypass grafting was implemented to reduce trauma of surgical coronary revascularization by avoiding extracorporeal circulation. TEA in combination with GA further reduces intraoperative stress resulting in more rapid extubation and significantly better pain relief in patients undergoing off-pump coronary artery bypass grafting (OPCAB). In addition, common postoperative complications are also decreased. Methodology: 40 male patients aged between 40-65 years with CAD undergoing OPCAB surgery at NICVD from April 2006 to October 2008 were randomly divided in two groups. Group A received epidural analgesic drugs through an indwelling catheter introduced before induction of anesthesia while group B patients received standard general anesthesia (GA) alone. Group A patients received continuous epidural analgesia delivered through the indwelling catheter with a mixture of Lignocaine (2%) 20 ml + Bupivacaine (0.5%) 20 ml + Fentanyl 50 gm 1 ml + normal saline q.v. 50 ml at the rate of 1-2 ml/hour by a syringe pump for up to 72 hours. Group B patients received conventional intermittent narcotics (Morphine)/NSAIDS (Ketorolac/Diclofen) for up to 72 hours. Results: Haemodynamic parameters of all patients in both the groups were within acceptable range throughout operations. Incidence of cardiac dysrhythmias was less in patients of group A. Group A patients showed faster recovery and better analgesia compared to Group B patients. There was also decreased incidence of nausea, vomiting, arrhythmia, O2 desaturation, confusional states, renal failure and requirement of iontropic support in ICU in Group A patients. TEA for postoperative analgesia was safe and well accepted by the patients. There was no complication related to epidural anesthesia in any patient. Conclusion: TEA in general anesthesia provides faster recovery and effective analgesia. Nonetheless, the actual and potential risks of TEA during cardiac surgery should not be underestimated. Keywords: Thoracic epidural anaesthesia; OPCAB; Postoperative analgesia DOI: 10.3329/cardio.v2i2.6632 Cardiovasc. j. 2010; 2(2) : 156-162